2019
DOI: 10.1016/j.foodhyd.2018.08.056
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun curcumin-loaded protein nanofiber mats as active/bioactive coatings for food packaging applications

Abstract: In this study, curcumin was encapsulated within electrospun protein (i.e. gelatin and zein) 15 fibers to generate bioactive coatings for food packaging. Additionally, a green tea extract (GTE) was also incorporated within the formulations to evaluate its impact on the stability, protective ability, and release properties of the curcumin-loaded fibers. Due to the poor solubility of curcumin in aqueous media, a strategy based on its incorporation through liposomes was developed, allowing to successfully incorpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(58 citation statements)
references
References 59 publications
3
55
0
Order By: Relevance
“…In addition to the fact quercetin and cellulose nanocrystals were incorporated at low concentrations, all coated composites presented similar spectra corresponding to zein characteristic bands. The main zein peaks were correlated to zein amides I, II, and III, respectively: (i) peak at 1647 cm −1 associated to C=O stretching vibration band of peptide groups with C-N stretching contributions; (ii) in the range of 1538 cm −1 , characterized by vibrations in the plane of N-H bond of peptide groups; and (iii) in the region of 1242 cm −1 and a set of band between 3100 and 2800 cm −1 , associated with C-H vibrations of CH 3 and CH 2 groups from fatty acids and side chains from amino acids [34]. Zein peaks at 1041-1237 cm −1 corresponded to C-N stretching and hydroxyl groups were also observed through a broad band with a peak at approximately 3288 cm −1 [35].…”
Section: Morphological Resultsmentioning
confidence: 99%
“…In addition to the fact quercetin and cellulose nanocrystals were incorporated at low concentrations, all coated composites presented similar spectra corresponding to zein characteristic bands. The main zein peaks were correlated to zein amides I, II, and III, respectively: (i) peak at 1647 cm −1 associated to C=O stretching vibration band of peptide groups with C-N stretching contributions; (ii) in the range of 1538 cm −1 , characterized by vibrations in the plane of N-H bond of peptide groups; and (iii) in the region of 1242 cm −1 and a set of band between 3100 and 2800 cm −1 , associated with C-H vibrations of CH 3 and CH 2 groups from fatty acids and side chains from amino acids [34]. Zein peaks at 1041-1237 cm −1 corresponded to C-N stretching and hydroxyl groups were also observed through a broad band with a peak at approximately 3288 cm −1 [35].…”
Section: Morphological Resultsmentioning
confidence: 99%
“…(hydroxyl and N-H stretching vibrations), 2974 cm -1 , 2951 cm -1 and 2898 cm -1 (C-H stretching vibrations of CH3 and CH2 aliphatic groups), the amide I peak (1655 cm -1 ) mainly ascribed to C=O stretching vibrations, the amide II peak (1544 cm -1 ), which arises from N-H bending and C-N stretching vibrations and the amide III peak ascribed to C-N stretching band at 1260 cm −1 (Alehosseini, Gómez-Mascaraque, Ghorani, & López-Rubio, 2019;Alehosseini, Gómez-Mascaraque, Martínez-Sanz, et al, 2019). In contrast with previous studies, no significant shifts were observed in these spectral bands independently of the final composition of the encapsulation structures and suggesting (from the position of the amide I band) that the conformation of the zein in the fiber structures consisted on α-helices and unfolded protein chains (Aceituno-Medina, Mendoza, Lagaron, & López-Rubio, 2013).…”
Section: Development and Characterization Of Active Fibers Containingmentioning
confidence: 99%
“…The latter has received increased attention in recent years due to its advantages, such as mild processing conditions (not requiring high temperatures for processing), versatility and possibility of using all food-grade materials. Electrohydrodynamic processing is a simple, costeffective, efficient, versatile, and scalable technology to manufacture dry nano-and microencapsulation structures in the form of fiber mats (electrospinning) or particulate powders (electrospraying), by subjecting a polymeric fluid to an external high-voltage electric field (Alehosseini, Gómez-Mascaraque, Martínez-Sanz, & López-Rubio, 2019). Some of the advantages of the nanofiber mats produced using electrospinning are that they possess a large surface to volume ratio, and the processing conditions can be tuned to modify the size and morphology of the structures obtained, giving rise to an intertwined porous fibrous structure.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, its bioavailability reaches only 1% after oral administration (Liu et al, 2016). Several delivery strategies have been employed to overcome these obstacles, such as designing emulsions (Ma, et al, 2017), micelles (Wang & Gao, 2018), hydrogels (Zheng, Zhang, Chen, Luo, & McClements, 2017) , nanoparticles (C. Tan, Xie, Zhang, Cai, & Xia, 2016), applying electrospun fibres (Alehosseini, Gomez-Mascaraque, Martinez-Sanz, & Lopez-Rubio, 2019), creating phospholipid complexes (Maiti, Mukherjee, Gantait, Saha, & Mukherjee, 2007) and using liposomal systems (Alavi, Haeri, & Dadashzadeh, 2017;Karewicz et al, 2013;Liu, Liu, Zhu, Gan, & Le, 2015;Pu, Tang, Li, Li, & Sun, 2019).…”
Section: Introductionmentioning
confidence: 99%